2005
DOI: 10.1007/s00420-004-0598-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on cadmium and tubular dysfunction markers in urine from adult women in non-polluted areas

Abstract: There were age-related increases in Cd and tubular dysfunction markers in urine among women in areas with no known Cd pollution. The increase was amplified two- or 1.4-times when CR or SG correction was applied, respectively. The observation suggests that care should be practiced in applying CR or SG correction, especially when evaluation of Cd exposure and resulting health effects is made among elderly populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 23 publications
2
13
1
Order By: Relevance
“…The slope of b 2 -MG cr with Cd cr was shallow (i.e., 10.8 lg b 2 -MG cr /lg Cd cr ) for the 5 prefectures in combination, as it was observed among the cases in non-polluted areas (i.e., -25 lg b 2 -MG cr /lg Cd cr ) in contrast to a sharp slope for those in polluted areas (6,194 lg b 2 -MG cr /lg Cd cr ) . The effects of age was essentially none in the present analyses possibly because the majority were at the ages of 40 and 50s, although it is known that the aged women tend to have higher Cd, a 1 -MG and b 2 -MG (Moriguchi et al , 2005. Effects of smoking on Cd could not be detected.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The slope of b 2 -MG cr with Cd cr was shallow (i.e., 10.8 lg b 2 -MG cr /lg Cd cr ) for the 5 prefectures in combination, as it was observed among the cases in non-polluted areas (i.e., -25 lg b 2 -MG cr /lg Cd cr ) in contrast to a sharp slope for those in polluted areas (6,194 lg b 2 -MG cr /lg Cd cr ) . The effects of age was essentially none in the present analyses possibly because the majority were at the ages of 40 and 50s, although it is known that the aged women tend to have higher Cd, a 1 -MG and b 2 -MG (Moriguchi et al , 2005. Effects of smoking on Cd could not be detected.…”
Section: Discussioncontrasting
confidence: 73%
“…a 1 -MG (mg/g cr) b 2 -MG NAG (Unit/g cr) Noonan et al (2002) 0.1 lg/g cr 120 lg/g cr 0.7 American (n = 144; probably men and women mixed) Satarug et al (2005) When similar (although not identical) data were employed in more than one study, priority was given to the study with more cases (e.g., Moriguchi et al 2005, rather than Moriguchi et al 2003Moriguchi et al , 2004 When the same data were presented in several units, e.g., as observed (per l) and after correction for CR (per g cr), priority was given to CRcorrected values for uniformity in the table (e.g., Reaves and Vanderpool 1997;Moriguchi et al 2005;Kowal and Zirkes 1983;Å kesson et al 2005;Suwazono et al 2006;Yamagami et al 2008) When values given in other units, e.g., in mmol, they were converted to lg/g cr by use of MW of 12.4 for Cd and 113.12 for creatinine (cr)…”
Section: CDmentioning
confidence: 99%
“…Criticism has been raised since early days on the adequacy of dividing urinary analyte level by creatinine concentration as a measure to correct for different urine density (e.g., Alessio et al 1985;Berlin et al 1985). This study group also observed that bias may be caused by creatinine correction in the evaluation of β 2 -MG-U (Ikeda et al 2003b), because creatinine concentration will decrease at advanced ages (Moriguchi et al 2004a) simultaneously with physiological increases in Cd-U and β 2 -MG-U (Moriguchi et al 2004b). It is nevertheless a common practice both in occupational and environmental health to express Cd-U and β 2 -MG-U levels as corrected for creatinine concentration (World Health Organization 1996;American Conference of Governmental Industrial Hygienists 2003).…”
Section: Discussionmentioning
confidence: 80%
“…It was not possible to control ages strictly, although participants were mostly women at middle ages. It was previously confirmed that aging in addition to gender influences urinary levels of Cd and tubular dysfunction markers [62][63][64] , and thus night induce bias in the evaluation 65) . The fourth limitation relates to the exposure-effect analysis.…”
Section: Discussionmentioning
confidence: 77%